Glycaemic status in patients of acute myocardial infarction: A detailed analysis. Issue 1 (January 2016) - Khan, Imran; Siddiqui, Anwar H.; Singhal, Sangeeta; Aslam, Mohd; Perwez, Anjum; Faraz, Ahmad
Abstract: Aims: Diabetes mellitus (DM) is considered to be one of the important risk factors for cardiac diseases. Frank diabetes is usually preceded by long term abnormality in glucose homeostasis which is called pre-diabetes. The hypothesis that diabetic patients have greater risk and worse prognosis of Acute Myocardial Infarction (AMI) than pre-diabetics is controversial. Considering that India has been declared as a diabetic capital of the world, the study aimed to assess the load of pre diabetics, diabetics and non-diabetics landing in myocardial infarction. Materials and methods: The study consisted of through physiological and biochemical evaluation of 200 patients of newly diagnosed AMI and evaluating the load of non-diabetics, pre-diabetics and diabetics among them. Result: It was found that the total non-diabetic population (normoglycaemic and pre-diabetic) formed the bulk of AMI patient (69%) in our study. The degree of biochemical alterations seen among the three groups suggests that abnormal glucose homeostasis is not the sole determinant of the severity of AMI. The study data also suggests that glycaemic status, which poses a risk for AMI, differs in male and female individuals. Males even with normal glucose level are at increased risk to develop MI. Conclusion: The study concludes that both males and females with their blood glucose in pre-diabetic range are seen to be vulnerable to develop AMI. Thus all individuals irrespective of their glycaemic status around the age of forty should be screened and individuals with fasting sugar in pre-diabetic range should take extra precaution in terms of healthy diet, life style and regular check up